A reprodução da violência doméstica e suas interfaces com a lógica da dominação - Melatti, Kelly Rodrigues (2011)
This current essay presents a systematization of our studies and researches about the reproduction of domestic violence perpetrated by mothers, from popular sections, against their children and the interfaces of this question with the logic of domination. Focusing efforts in the attempt to identify the reasons that lead mothers, in the condition of caretakers, to commit violence against their children., based in yours narratives and memories, permeated by the meanings that they attributed to their own experiences, they contributed to the qualitative analysis of the this research. The categories identified by the transcriptions pointed out the specificity of the social class in the context of domestic assault reproduction, the logic of capitalism reproduction and the patriarch thought schemes were emphasized as a remarkable characteristic in the context of these women s life. Beginning with the presuppose that the reproduction of the domestic assault has a function in the production and in the reproduction of the capitalism productive way, in the ideology of maintenance and ratification of the dominant class interests, we identify that the violence is part of the capitalist society structure, a expression of the social matter and assaults, in a ethic disrespect, all social beings that, reduced to the condition of objects in their relationships, reproduce the violence immediately and superficially in the quotidian. In this way, there is a stress to the need of mediation that promotes general reflection in our society in the pursuit of acknowledge the individual as a social being, free for their own choices